Perspectives on the movimento” Billings i want you to live” in the recovery of Billings reservoir - Almeida, Thereza de Carvalho; Almeida, Daniel Ladeira; Neves, Paulo Dias (Revista Hipótese, 2018)
This article was structured through the analysis of governmental initiatives, publications of regional circulation and debates pertinent to the theme, with the objective of analyzing effective proposals of recovery of the dam listed by Movimento Billings I want you alive. The results of the analyzes allowed to contrast the reports and debates with the regional publications, which identified a slowing of the governmental actions in relation to the recovery of the Billings reservoir.